The activities of selected metals and supports for CO2 hydrogenation to methanol: A review - Tani J. Monene; Mduduzi N. Cele (Applied Catalysis O: Open)
CO2 hydrogenation to methanol is a promising alternative for lowering atmospheric CO2 while continuously producing chemicals, fuel, and energy for our modern world. Catalysts play a significant role because of the thermodynamic stability of CO2 and H2 activation. Catalysts provide active metal and basic sites for CO2 adsorption for activation by bending the linear CO2 molecule. Excited hydrogen ions are produced from H2 homolytic and heterolytic dissociation on the surface of the catalysts depending on the structure and the nature of the material. This review highlights the importance of metal-support interactions because they affect the hydrogenation rate and methanol selectivity. Various metals (Cu, Ni, etc.), supports (Metal oxides, Mixed oxides, MOFs, Metal sulfide, etc.) and the influence of catalysts synthesis method (Co-precipitation, Solvo/Hydrothermal, Impregnation, etc.) reported in CO2 hydrogenation to methanol are reviewed.